Sosialisasi Pentingnya Pendidikan dan Pemanfaatan Teknologi Informasi di Bidang Pendidikan - Amalia Agung Septarina; Anisa Hudi Widaningrum; Novia Ratnasari; Rachmad Imam Tarecha; Pangestuti Prima Darajat (I-Com: Indonesian Community Journal, 2024)
The lack of interest of Dusun Lebaksari residents to continue their education to higher education needs to be followed up. This is caused by economic factors and lack of support from parents. This socialization aims to encourage community motivation to consider educating their children up to higher education level. So that it can produce the younger generation who can make a major contribution to the nation by utilizing information technology to maximize their learning process. The activity held at SDN Kepatihan 3 was attended by the Head of Dusun Lebaksari, teachers and guardians of elementary school students grades 1 to 6. The method used in this activity was the Community Education method through socialization with several stages, that are field survey, preparation and socialization. The results of this activity increase participants understanding of the importance of education and provide an illustration that achieving higher education does not always require a lot of money because it can be done through scholarships.